Social Justice and Health Equity in the Teaching and Learning Environment: Perspectives of Academic Leaders in Health Profession Education Programmes - Benita Cohen; Debra Beach Ducharme; Moni Fricke; Alan Katz; Laura MacDonald; Donna Martin; Christen Rachul; Gayle Restall; Dana Turcotte (Canadian Journal for the Scholarship of Teaching and Learning)
It is the responsibility of all health profession education programmes to prepare their graduates to champion social justice and health equity (SJ/HE) within and beyond the healthcare system. However, little is known about the perspectives of educational leaders within health professional programmes regarding the teaching and learning environment (TLE) with respect to SJ/HE. The objective of this study was to explore the perspectives of health profession education leaders about their individual and collective vision for a TLE that promotes SJ/HE and its actualization. A qualitative descriptive approach was utilized to gather, synthesize and make meaning of the perspectives of academic leaders in one Canadian health professional faculty. Using semi-structured interviews, participants (n=14) representing five different colleges including medicine, nursing, oral health, pharmacy, and rehabilitation sciences, were interviewed in-person in the academic setting. Following inductive thematic analysis, one overarching theme resulted, “We Need to Walk the Talk.” Five sub-themes also emerged, including understanding of SJ/HE; the current TLE; facilitators and barriers to a TLE promoting SJ/HE; and actions required to further develop a TLE promoting SJ/HE. Academic leaders expressed hope and willingness to create a TLE that promotes SJ/HE, acknowledging that there was a lot to be done and a unified vision for the faculty is important. The results of this study underscore the need for academic leaders to have a clear and unified articulation of a TLE that embodies SJ/HE for all.